1998
DOI: 10.2116/analsci.14.375
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Separation of (R,S)-1,1′-Binaphthyl-2,2′-diyl Hydrogenphosphate by Capillary Electrophoresis Using Monosaccharides as Chiral Selectors

Abstract: Capillary electrophoresis (CE) is a powerful tool for the resolution of enantiomeric compounds owing to its high separation efficiency and its facility to use a wide variety of chiral separation media. [1][2][3][4] In addition to cyclodextrins, which are the cyclic a-1,4-linked oligosaccharides most frequently used as chiral selectors, some linear oligosaccharides have been recently utilized for the separation of optical isomers by CE. [5][6][7][8][9][10][11][12] Kano et al. 10 have reported that the chiral se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The distribution of Dserine in rat brain was determined. Previous publications that utilized saccharides as chiral selectors demonstrated that a combination of hydrophobic interactions and hydrogen bonding are responsible for chiral recognition [169] with specific requirements for D-glucose chiral selectivity being that the C-1 oxygen is in the a-configuration, the C-4 hydroxyl group is oriented downward, and that either a methyl or hydroxymethyl group be present at C-5 [170].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The distribution of Dserine in rat brain was determined. Previous publications that utilized saccharides as chiral selectors demonstrated that a combination of hydrophobic interactions and hydrogen bonding are responsible for chiral recognition [169] with specific requirements for D-glucose chiral selectivity being that the C-1 oxygen is in the a-configuration, the C-4 hydroxyl group is oriented downward, and that either a methyl or hydroxymethyl group be present at C-5 [170].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The same author [378] studied the influence of the kind of linkage of different malto-and oligosaccharides on the enantioselectivity. Nakamura et al [379] showed that even monosaccharides such as d-glucose, d-mannose and some of their derivatives can exhibit some limited chiral recognition ability.…”
Section: Neutral CD Derivatives a Great Variety Of Neutral Derivativmentioning
confidence: 99%
“…The enantiomers were separated with various CDs, e.g., native [16,17] and sulfated CDs [18], heptakis(6-hydroxyethylamino-6-deoxy)-b-CD [19], maleic acid derivative of b-CD [20], CDs in combination with bile salts [21,22], and quaternary ammonium b-CDs in nonaqueous CE [23]. Separation was also performed with noncyclic saccharides, such as mono- [24], di- [25] and polysaccharides [26,27]. As a consequence of the aforementioned findings, the purpose of this study was to investigate the influence of the degree and position of methylation of b-CD on the resolution of BNP enantiomers.…”
Section: Introductionmentioning
confidence: 99%